PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS KELAUTAN DAN PERIKANAN PROVINSI KALIMANTAN BARAT - B11109065, MEIRDIA ERIANI (Jurnal Manajemen Update, 2015)
Training is an educational process in which there is a learning process that is carried out short-term and aims to improve the knowledge, attitudes and skills. Additionally, employees need a good motivation from within themselves and from institutions. Thus the higher the sense of motivated higher the level of performance. The purpose of this study to determine the effect of training and motivation on employee performance Department of Marine and Fisheries of West Kalimantan Province.The population of this study were employees of the Department of Marine and Fisheries of West Kalimantan Province who have completed the training, amounting to 50 people. While the samples taken in this study is a member selected from the population that were numbered 50 people. Based on the research, there is positive and significant relationship between training and motivation on employee performance. Value of coefficient of determination (Adjusted R Square) is equal to 0.390, meaning that the variable employee performance can be affected by variables of training and motivational variables by 39% , while the remaining 61% is contributed by the other independent variables are not included in this study. Keywords: Training, Motivation, Performance